A model for the motivation of teaching staff in higher education institutions analyzed from the complexity - Franco-López, Jorge Ariel (2024)
Objective. This study aims to develop a model that provides a better understanding of the motivation of teaching staff in higher education institutions (HEI) from a complexity perspective. Methodology. It is a correlational-descriptive type of research, with a mixed research method and a motivation-dependent category. The research is linked to a categorical system extracted from the literature review and subsequently refined by two rounds of experts using the Delphi technique. They indicated the following 6 categories that influence teaching motivation: intrinsic, extrinsic, transform knowledge, generate research, quality in education, permanent education, and teaching as a generator of social status. Subsequently, 40 referenced subcategories were constructed that account for each category. For greater accuracy, the Lasso method was used to narrow down the subcategories to 27; this ensured the formulation of questions in a survey with 122 records of teachers, based on the Likert scale type. Results. The interdisciplinarity of complex thinking requires several factors in motivating higher education faculty. These include professional activity, comprehensiveness, effectiveness, knowledge, problem-solving, leadership, interactions, autonomous learning, methodologies, institutional issues, power relations, and social position. Discussion and conclusion. It is crucial to start from a holistic view that integrates teaching motivation in different aspects such as teaching practice, student behavior, organizational aspects, interactivity of the academic community, recognition, and historical and situational contexts. Equally crucial is achieving the integration of these elements that contribute to fostering quality training processes.